COMMON SLAVONIC SOCIAL VALUES IN TERMS OF METHODS OF TEACHING THE RUSSIAN LANGUAGE - S V Nikolaenko (Russian Language Studies, 2015)
The article describes the main approaches of the study of the concept of ‘values’: in terms of cultural linguistics, sociolinguistics and pedagogy. Methodological support required when working at the lessons of the Russian language in order to create sustainable social axiological orientations for students has been developed. The practical tasks aimed at building the moral stand of the coordinate system at school have been presented.